2008
DOI: 10.1080/09638280701785866
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon ossification: Pathology, imaging and aetiology

Abstract: The Achilles tendon usually responds to an insult with the development of mature bone, not dystrophic calcification, with no evidence of inflammatory or degenerative changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 21 publications
0
55
0
Order By: Relevance
“…• Acute Achilles tendon rupture 2,109 • Partial tear of the Achilles tendon 52 • Retrocalcaneal bursitis 47 • Posterior ankle impingement 113 • Irritation or neuroma of the sural nerve 2 • Os trigonum syndrome 80 • Accessory soleus muscle 67 • Achilles tendon ossification 105 • Systemic inflammatory disease 7 • Insertional Achilles tendinopathy Clinicians should consider diagnostic classifications other than Achilles tendinopathy when the patient's reported activity limitations or impairments of body function and structure are not consistent with those presented in the diagnosis/classification section of this guideline, or, when the patient's symptoms are not resolving with interventions aimed at normalization of the patient's impairments of body function.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…• Acute Achilles tendon rupture 2,109 • Partial tear of the Achilles tendon 52 • Retrocalcaneal bursitis 47 • Posterior ankle impingement 113 • Irritation or neuroma of the sural nerve 2 • Os trigonum syndrome 80 • Accessory soleus muscle 67 • Achilles tendon ossification 105 • Systemic inflammatory disease 7 • Insertional Achilles tendinopathy Clinicians should consider diagnostic classifications other than Achilles tendinopathy when the patient's reported activity limitations or impairments of body function and structure are not consistent with those presented in the diagnosis/classification section of this guideline, or, when the patient's symptoms are not resolving with interventions aimed at normalization of the patient's impairments of body function.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…A recent review article on Achilles tendon mineralization concluded that the tendo Achilles can respond to an insult with the development of mature bone, with no evidence of inflammatory or degenerative changes at the time of biopsy. 4 The etiology most commonly implicated is either a traumatic incident or surgery. 4 Studies have shown the incidence of postoperative mineralization after open tendon repair ranges from 14.4--28%.…”
Section: Introductionmentioning
confidence: 99%
“…4 The etiology most commonly implicated is either a traumatic incident or surgery. 4 Studies have shown the incidence of postoperative mineralization after open tendon repair ranges from 14.4--28%. 6,7 The development of mineralization has a negative effect on clinical outcome, especially with lesions larger than 10 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually associated with surgical intervention or trauma [9] and is more commonly seen in the Achilles tendon [10] or following repair of ruptured distal biceps [11]. To our knowledge, there is no description of OT as a complication of calcifying tendinitis of the rotator cuff.…”
Section: Introductionmentioning
confidence: 99%